2003
DOI: 10.1037/0278-6133.22.5.464
|View full text |Cite
|
Sign up to set email alerts
|

A connectionist implementation of the theory of planned behavior: Association of beliefs with exercise intention.

Abstract: The theory of planned behavior suggests attitudes are a product of salient beliefs. This study examined whether aggregating salient beliefs was plausible within a more biologically centered information-processing environment. A neural network was used to examine associations among beliefs relating to exercise intention. Data on intentions and behavioral, normative, and control beliefs from 114 respondents were used to train (by error backpropagation) a neural network to associate beliefs with intention. The R-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Additionally, explicit comparisons of linear and nonlinear analytical approaches have shown that the fit of the latter is better than that of the former; nonlinear models can explain more variance in outcomes compared to their linear equivalents (e.g., Lowe et al, 2003).…”
Section: Uncertainty 1: Nonlinear Work-health Relationshipsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, explicit comparisons of linear and nonlinear analytical approaches have shown that the fit of the latter is better than that of the former; nonlinear models can explain more variance in outcomes compared to their linear equivalents (e.g., Lowe et al, 2003).…”
Section: Uncertainty 1: Nonlinear Work-health Relationshipsmentioning
confidence: 99%
“…True nonlinear models express nonlinearity in the parameters of the variables. Additional shortcomings of linear regression (Bansal et al, 1993;Lind & Sulek, 2001;Lowe et al, 2003) render it inappropriate for addressing nonlinear phenomena.…”
Section: The Present Studymentioning
confidence: 99%
See 3 more Smart Citations